MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Mitigating overload conditions in vibrating screens through fuzzy-controlled feed rate regulation - Alexandre G. Fonseca; Robson A. Duarte; Kaike S. Albuquerque; Thomás Pinto; Thiago A.M. Euzébio (Minerals Engineering, 2026)

Genomic Insights into a New Burkholderia cenocepacia Sequence Type Linked to Cepacia Syndrome in Cystic Fibrosis - Tatiane S. Xavier; Felipe A. Simão; Heloisa S. Rosa; Jade C. S. Colomer; Renata W. Cohen; Tânia W. Folescu; Ana Paula D’A. Carvalho-Assef; Robson S. Leão; Elizabeth A. Marques (Current Microbiology, 2026)
Burkholderia cenocepacia is an important pathogen in cystic fibrosis (CF) patients, responsible for chronic lung infections and, in severe cases, cepacia syndrome (CS), characterized by necrotizing pneumonia, bacteremia, and high mortality. Epidemic lineages, such as B. cenocepacia J2315 (ET12) and ST32, are highly transmissible and frequently associated with CS. In this study, five B. cenocepacia isolates recovered from sputum and blood samples of a pediatric CF patient who developed CS were sequenced and analyzed in silico using multilocus sequence typing (MLST), phylogenomics, genomic similarity metrics, and comparative genomics to identify virulence determinants, resistance genes, and mobile genetic elements. A novel sequence type (ST2424), not associated with any known clonal complex, was identified. Phylogenomic analysis revealed high genetic relatedness among the isolates, consistent with a monoclonal infection undergoing within-host microevolution. Comparative analyses revealed distinct genetic profiles: aaiB (T6SS) was present in all isolates, whereas narG and manCcore were exclusive to bloodstream isolates. Acquired resistance determinants, including bla OXA−1043 , sul1 , aac(6′)-IIc , and aadA1 , were detected and were absent from the reference strains B. cenocepacia J2315 and ST32. Mobile genetic elements, including insertion sequences from the IS3, IS5, and IS200/IS605 families, as well as a putatively conjugative plasmid encoding Tra/Trb subunits of the type IV secretion system, were also identified. These findings describe a novel B. cenocepacia sequence type associated with fatal CS and highlight the high genomic plasticity of this species, reinforcing the importance of genomic surveillance to detect emerging variants and improve clinical management in CF.

The nonpeptide angiotensin-(1–7) mimic AVE0991 attenuates neuroendocrine and behavioral responses to chronic unpredictable stress - Maria Luiza Antunes Fonseca; Laura Beatriz de Oliveira Amaral; Sthéfanie C. A. Gonçalves; Laura A. Costa; Laura Barroso Ferreira de Oliveira; Flávio A. G. Mourão; Marco Antônio Peliky Fontes; Michael Bader; Robson A. S. Santos; Maria José Campagnole-Santos; Lucas M. Kangussu (Psychopharmacology, 2026)
Rationale Chronic stress, frequently associated with dysfunction of the hypothalamic–pituitary–adrenal (HPA) axis and reduced neuroplasticity, is a major risk factor for psychiatric disorders such as anxiety and depression. Objective The present study aimed to validate a 21-day chronic unpredictable stress (CUS) model and to investigate the effects of the Mas receptor agonist AVE0991 on stress-induced behavioral and molecular alterations. Methods Male C57BL/6J mice were exposed to a 21-day CUS protocol. Animals were randomly assigned to four groups: control + saline, CUS + saline, control + AVE0991, and CUS + AVE0991 (3 mg/kg, i.p .). AVE was administered daily during the last two weeks of the stress protocol. Behavioral tests were performed to evaluate anxiety- and depressive-like behaviors, and plasma corticosterone, blood glucose levels, and brain-derived neurotrophic factor (BDNF) levels in the prefrontal cortex, hippocampus, and hypothalamus were measured. Results CUS exposure significantly increased plasma corticosterone and glucose levels and induced anxiety- and depressive-like behaviors. Stressed animals also showed reduced BDNF levels in the prefrontal cortex, hippocampus, and hypothalamus. Treatment with AVE0991 attenuated the increase in corticosterone and prevented stress-induced hyperglycemia. Moreover, AVE0991 reduced depressive-like behavior, increased latency to immobility, and improved anxiety-related parameters in the elevated plus maze and open field tests without affecting locomotor activity. AVE0991 also prevented the reduction of BDNF levels in stress-exposed animals. Conclusion These findings validate the CUS model and demonstrate that activation of the Mas receptor by AVE0991 exerts anxiolytic, antidepressant, and neuroprotective effects, supporting its potential as a therapeutic strategy for stress-related neuropsychiatric disorders.

Coat characteristics, physiological traits, serum metabolites, and thyroid hormones of Canindé and Moxotó goats in a semiarid environment - Wallace S. Tavares da Silva; Robson M. Freitas Silveira; Jacinara H. Gurgel Morais Leite; Concepta McManus; Débora A. Evangelista Façanha (Tropical Animal Health and Production, 2026)
This study evaluated the adaptive responses of dark-coated Canindé and light-coated Moxotó goats reared under semiarid conditions in Brazilian semiarid through an integrated assessment of thermoregulatory, biochemical, hormonal, and morphological variables. Sixty non-pregnant and non-lactating goats (30 Canindé and 30 Moxotó) were evaluated during summer and winter under the same grazing and management conditions. Animals received native pasture and concentrate supplementation (200 g/head/day). Significant breed × season interactions ( P < 0.05) were observed for physiological, metabolic, hormonal, and coat variables. Dark-coated Canindé goats showed higher coat surface temperature and greater seasonal variation in coat thickness (0.60 vs. 0.51 mm), as well as marked seasonal changes in T4 (1.67 vs. 4.47 µg/dL), glucose (48.87 vs. 105.03 mg/dL), and albumin (4.42 vs. 8.19 mg/dL) from summer to winter, indicating greater metabolic flexibility. In contrast, light-coated Moxotó goats maintained lower and more stable thyroid hormone concentrations across seasons (T4: 1.63 vs. 1.63 µg/dL) and exhibited increased creatinine levels during winter (0.95 vs. 1.57 mg/dL), suggesting a more conservative adaptive strategy. Multivariate analyses demonstrated distinct adaptive profiles between breeds. Factor analysis revealed integration between thermoregulation and metabolism in Canindé goats, whereas Moxotó goats showed stronger biochemical compensation mechanisms. Decision tree analysis identified globulin and coat thickness as the main discriminating variables between breeds and seasons. These findings demonstrate that locally adapted goat breeds use distinct but effective adaptive strategies to cope with semiarid environmental conditions and provide important phenotypic indicators to support conservation programs, breed selection, and climate-resilient small ruminant production systems.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

OnabotulinumtoxinA Inhibits Dysregulation of Descending Pain Modulation Following Mild Traumatic Brain Injury in Mice - Robson C. Lillo Vizin; Caroline M. Kopruszinski; Janice N. Oyarzo; David W. Dodick; Ron S. Broide; Amy D. Brideau-Andersen; Mitchell F. Brin; Trent Anderson; Edita Navratilova; Frank Porreca (Toxicon, 2026)

Simultaneous monitoring of electrogenerated H2O2 and paracetamol degradation via electrochemical flow reactor with flow injection analysis - Robson S. Souto; Anderson M. Santos; Willyam R.P. Barros; Marcos R.V. Lanza (Chemical Engineering Journal, 2026)

Warmer climate threatens the occurrence of giant trees in the Amazon basin - Robson Borges de Lima; Cinthia Pereira de Oliveira; Diego Armando S. da Silva; Daniela Granato-Souza; Lorrayne Aparecida Gonçalves; Caroline C. Vasconcelos; Anderson Pedro B. Batista; João Ramos de Matos Filho; Joselane P. Gomes da Silva; Perseu da Silva Aparício; Carla S. Campelo de Souza; Jadson Coelho de Abreu; et al. (Journal of Environmental Management, 2026)

Mas Knockout Mice Present Altered Behavioral and Neuroendocrine Coping Responses to Chronic Unpredictable Stress - Sthéfanie C. A. Gonçalves; Andressa da Silveira Silva; Bruna Karen Oliveira Nogueira; Flávio A. G. Mourão; Marco Antônio Peliky Fontes; Michael Bader; Robson A. S. Santos; Maria José Campagnole-Santos; Lucas M. Kangussu (Molecular Neurobiology, 2026)
Stress is defined as a disruption of homeostasis that elicits adaptive responses aimed at restoring physiological balance. However, when stress becomes chronic or overwhelming, maladaptive changes may occur, contributing to endocrine, behavioral, and neuropsychiatric dysfunctions. Beyond the classical neuroendocrine axes, such as the sympatho-adrenomedullary and hypothalamic–pituitary–adrenal (HPA) axes, the renin-angiotensin system has also being implicated in stress modulation. Previous studies have shown that angiotensin-(1–7), acting through its receptor Mas, exerts a modulatory effect on the stress response, attenuating anxiety- and depression-like behaviors induced by various stressors. Here we investigated the impact of genetic deletion of Mas on the consequences of chronic unpredictable stress (CUS) exposure. Over 21 consecutive days, mice were subjected to random stressors, after which endocrine, behavioral and neurochemical assessments were performed. Mas knockout (KO) mice exposed to CUS exhibited significantly elevated corticosterone and blood glucose levels compared to stressed wild-type mice. In behavioral tests, stressed Mas KO mice displayed the highest immobility times in the forced swimming test, indicating enhanced depressive-like behavior. Anxiety-like behavior was also heightened in Mas KO mice, as evidenced by a significant reduction in the percentage of time spent in the open arms of the elevated plus maze test. Neurochemical analysis revealed a marked reduction in brain-derived neurotrophic factor (BDNF) levels in key brain regions of stressed Mas KO animals. Together, these findings suggest that Mas plays a critical role in the neurobiology of stress, since its absence exacerbates HPA axis hyperactivity, depression- and anxiety-like behaviors, as well as BDNF reduction. Overall, these results highlight the potential neuroprotective role of Mas in stress-related disorders.

Coat traits, skin evaporation, and milk production of Majorera and Palmera goats in a temperate region - Wallace S. T. da Silva; Robson Mateus Freitas Silveira; Wilma E. da Silva; Jacinara H. G. M. Leite; Luis A. Bermejo; Concepta McManus; Alexandr T. Krupij; Débora A. E. Façanha (International Journal of Biometeorology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Intercultural networks deepen learning for transformative sustainability education: lessons from co-designing transdisciplinary international learning labs - Danielle S Spence; Maureen G Reed; James P Robson; Bianca Currie; Eureta Rosenberg; Marlis Merry; Jana Gengelbach (Current Opinion in Environmental Sustainability, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Evolved bet-hedging through maternal effects: developmental trajectory variation in annual killifish across a wet–dry cycle - Vinicius Weber; Felipe Alonso; Robson S. Godoy; Luis E. K. Lanés; Mateus M. Pires; Adriana Gava; Cristina Stenert; Leonardo Maltchik (Hydrobiologia, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Integrated system for in situ generation and online monitoring of H2O2: Coupling an electrochemical flow reactor to a flow injection analysis system - Anderson M. Santos; Robson S. Souto; Willyam R.P. Barros; Marcos R.V. Lanza (Process Safety and Environmental Protection, 2025)

Genomic and phenotypic insights into Serratia interaction with plants from an ecological perspective - Ubiana C. Mourão Silva; Daliane R. C. da Silva; Sara Cuadros-Orellana; Leandro M. Moreira; Laura R. Leite; Julliane D. Medeiros; Erica B. Felestrino; Washington L. Caneschi; Nalvo F. Almeida; Robson S. Silva; Christiane A. Oliveira-Paiva; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2025)

Electrochemical degradation of tebuthiuron pesticide using a flow reactor: Insights into the co-generation of oxidants and ecotoxicological risks - Robson S. Souto; Isaac Sánchez-Montes; Géssica O.S. Santos; Paulo J.M. Cordeiro-Junior; Renata Colombo; Mauro C. Santos; Marcos R.V. Lanza (Journal of Environmental Chemical Engineering, 2025)

Biogeographical Origins of Caatinga Squamata Fauna - Castiele Holanda Bezerra; Antonio Rafael Lima Ramos; João Fabrício Mota Rodrigues; Fernanda A. S. Cassemiro; Robson Waldemar Ávila (Journal of Biogeography, 2025)
Aim Several lines of evidence have noted that open vegetation biomes in the Neotropics are younger than moist forests, leading us to question which historical processes shaped the current species distribution patterns in these new biome formations. Here we investigate the temporal patterns of speciation and colonisation from surrounding biomes (Amazonia, Atlantic Forest and Cerrado) in the Caatinga historical assembly of squamate species, to understand the role of geomorphological events and climate change in driving its diversification. Location Neotropics. Taxon Squamata (snakes, lizards and amphisbaenians). Methods We used a phylogenetic tree and occurrence data for 459 squamate species distributed throughout four different biomes (Amazonia, Atlantic Forest, Cerrado and Caatinga) to reconstruct ancestral geographic ranges using the R package BioGeoBEARS. We used BAMM to estimate the rates of species diversification. Results Our results indicate that the current diversity patterns of squamates in the Caatinga were a result of pervasive faunal exchanges from adjacent biomes since the Paleogene, with similar numbers of dispersal events in each source area. The Neogene period was determinant in the diversification process, leading to the current assembly patterns of this group in the Caatinga. Main Conclusions The landscape transformation and climate change that increased aridity in northeastern Brazil probably shaped the diversification of dry‐adapted squamates in the Caatinga, like tropidurid lizards. However, the Pleistocene climatic fluctuations associated with the highly heterogeneous gradients of topography, geology, soils, climatic conditions, and different vegetation physiognomies could have facilitated faunal exchange with their neighbouring forested biomes, explaining the current presence of some typical forested lineages inside the Caatinga domain and help us to clarify the current distribution patterns of squamates in this region.

Corrigendum to “Plastic-degrading microbial communities reveal novel microorganisms, pathways, and biocatalysts for polymer degradation and bioplastic production” [Sci. Total Environ. 949 (2024) 174876] - Ellen Karen Barreto Roman; Murilo Antonio Ramos; Geizecler Tomazetto; Bruno Botega Foltran; Matheus Henrique Galvão; Iara Ciancaglini; Robson Tramontina; Felipe de Almeida Rodrigues; Larissa Soares da Silva; Ana Luiza Hernandes Sandano; Diógenes G. da S. Fernandes; Dnane Vieira Almeida; et al. (Science of The Total Environment, 2024)

Plastic-degrading microbial communities reveal novel microorganisms, pathways, and biocatalysts for polymer degradation and bioplastic production - Ellen Karen Barreto Roman; Murilo Antonio Ramos; Geizecler Tomazetto; Bruno Botega Foltran; Matheus Henrique Galvão; Iara Ciancaglini; Robson Tramontina; Felipe de Almeida Rodrigues; Larissa Soares da Silva; Ana Luiza Hernandes Sandano; Diógenes G. da S. Fernandes; Dnane Vieira Almeida; et al. (Science of The Total Environment, 2024)

Literature review on deep learning for the segmentation of seismic images - Bruno A.A. Monteiro; Gabriel L. Canguçu; Leonardo M.S. Jorge; Rafael H. Vareto; Bryan S. Oliveira; Thales H. Silva; Luiz Alberto Lima; Alexei M.C. Machado; William Robson Schwartz; Pedro O.S. Vaz-de-Melo (Earth-Science Reviews, 2024)

Angiotensin-(1–7) decreases inflammation and lung damage caused by betacoronavirus infection in mice - Erick Bryan de Sousa Lima; Antônio Felipe S. Carvalho; Isabella Zaidan; Adelson Héric A. Monteiro; Camila Cardoso; Edvaldo S. Lara; Fernanda S. Carneiro; Leonardo C. Oliveira; Filipe Resende; Felipe Rocha da Silva Santos; Luiz Pedro Souza-Costa; Ian de Meira Chaves; et al. (Inflammation Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Difference in Dietary Behaviors Between Children with and Without Neurodevelopmental Disabilities: Results from the 2022 National Survey of Children’s Health - S. Robson; L. Krott; C. Baker-Smith; A. Bhat; F. Patterson; B. Brewer (Journal of the Academy of Nutrition and Dietetics, 2024)

Methylphenidate Exposing During Neurodevelopment Alters Amino Acid Profile, Astrocyte Marker and Glutamatergic Excitotoxicity in the Rat Striatum - Felipe Schmitz; Luz Elena Durán-Carabali; Alessandra Schmitt Rieder; Josiane S. Silveira; Osmar Vieira Ramires Junior; Larissa D. Bobermin; André Quincozes-Santos; Vinícius S. Alves; Robson Coutinho-Silva; Luiz Eduardo B. Savio; Daniella M. Coelho; Carmen R. Vargas; et al. (Neurotoxicity Research, 2024)

Genomic Comparative of Pseudomonas aeruginosa Small Colony Variant, Mucoid and Non-mucoid Phenotypes Obtained from a Patient with Cystic Fibrosis During Respiratory Exacerbations - Mila M. Almeida; Leonardo R. Bastos; Mônica C. Firmida; Rodolpho M. Albano; Elizabeth A. Marques; Robson S. Leão (Current Microbiology, 2024)

Chromosomal structural rearrangements implicate long non-coding RNAs in rare germline disorders - Rebecca E. Andersen; Ibrahim F. Alkuraya; Abna Ajeesh; Tyler Sakamoto; Elijah L. Mena; Sami S. Amr; Hila Romi; Margaret A. Kenna; Caroline D. Robson; Ellen S. Wilch; Katarena Nalbandian; Raul Piña-Aguilar; et al. (Human Genetics, 2024)
In recent years, there has been increased focus on exploring the role the non-protein-coding genome plays in Mendelian disorders. One class of particular interest is long non-coding RNAs (lncRNAs), which has recently been implicated in the regulation of diverse molecular processes. However, because lncRNAs do not encode protein, there is uncertainty regarding what constitutes a pathogenic lncRNA variant, and thus annotating such elements is challenging. The Developmental Genome Anatomy Project (DGAP) and similar projects recruit individuals with apparently balanced chromosomal abnormalities (BCAs) that disrupt or dysregulate genes in order to annotate the human genome. We hypothesized that rearrangements disrupting lncRNAs could be the underlying genetic etiology for the phenotypes of a subset of these individuals. Thus, we assessed 279 cases with BCAs and selected 191 cases with simple BCAs (breakpoints at only two genomic locations) for further analysis of lncRNA disruptions. From these, we identified 66 cases in which the chromosomal rearrangements directly disrupt lncRNAs. In 30 cases, no genes of any other class aside from lncRNAs are directly disrupted, consistent with the hypothesis that lncRNA disruptions could underly the phenotypes of these individuals. Strikingly, the lncRNAs MEF2C-AS1 and ENSG00000257522 are each disrupted in two unrelated cases. Furthermore, we experimentally tested the lncRNAs TBX2-AS1 and MEF2C-AS1 and found that knockdown of these lncRNAs resulted in decreased expression of the neighboring transcription factors TBX2 and MEF2C , respectively. To showcase the power of this genomic approach for annotating lncRNAs, here we focus on clinical reports and genetic analysis of seven individuals with likely developmental etiologies due to lncRNA disruptions.

Genetic determinants of antimicrobial resistance in polymyxin B resistant Pseudomonas aeruginosa isolated from airways of patients with cystic fibrosis - Felipe A. Simão; Mila M. Almeida; Heloísa S. Rosa; Elizabeth A. Marques; Robson S. Leão (Brazilian Journal of Microbiology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Effect of Quinolinic Acid on Behavior, Morphology, and Expression of Inflammatory/oxidative Status in Rats’ Striatum: Is Coenzyme Q10 a Good Protector? - Fernanda Silva Ferreira; Osmar Vieira Ramires Junior; Tiago Marcon dos Santos; Josiane Silva Silveira; Bruna Ferrary Deniz; Vinícius Santos Alves; Robson Coutinho-Silva; Luiz Eduardo Baggio Savio; Angela T. S. Wyse (Neurotoxicity Research, 2023)

Microplastics and nanoplastics in haemodialysis waters: Emerging threats to be in our radar - Robson S. Passos; Andrew Davenport; Rosa Busquets; Clare Selden; Luiz B. Silva; J. Santos Baptista; Damià Barceló; Luiza C. Campos (Environmental Toxicology and Pharmacology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Physiological properties of the visual system in the Green Weaver ant, Oecophylla smaragdina - Yuri Ogawa; Lochlan Jones; Laura A. Ryan; Simon K. A. Robson; Nathan S. Hart; Ajay Narendra (Journal of Comparative Physiology A, 2023)
The Green Weaver ants, Oecophylla smaragdina are iconic animals known for their extreme cooperative behaviour where they bridge gaps by linking to each other to build living chains. They are visually oriented animals, build chains towards closer targets, use celestial compass cues for navigation and are visual predators. Here, we describe their visual sensory capacity. The major workers of O. smaragdina have more ommatidia (804) in each eye compared to minor workers (508), but the facet diameters are comparable between both castes. We measured the impulse responses of the compound eye and found their response duration (42 ms) was similar to that seen in other slow-moving ants. We determined the flicker fusion frequency of the compound eye at the brightest light intensity to be 132 Hz, which is relatively fast for a walking insect suggesting the visual system is well suited for a diurnal lifestyle. Using pattern-electroretinography we identified the compound eye has a spatial resolving power of 0.5 cycles deg −1 and reached peak contrast sensitivity of 2.9 (35% Michelson contrast threshold) at 0.05 cycles deg −1 . We discuss the relationship of spatial resolution and contrast sensitivity, with number of ommatidia and size of the lens.

Toxicological aspect of water treated by chlorine-based advanced oxidation processes: A review - Isaac Sánchez-Montes; Géssica O.S. Santos; Alexsandro J. dos Santos; Carlos H.M. Fernandes; Robson S. Souto; Pamela Chelme-Ayala; Mohamed Gamal El-Din; Marcos R.V. Lanza (Science of The Total Environment, 2023)

Rotational horse grazing and dry weather maximize infiltration into soil macropores - Laura B. Kenny; Daniel Giménez; Joshua S. Caplan; Ali Al-Sarraji; Mohson AlHello; Mark G. Robson; William Meyer; Carey A. Williams (Soil and Tillage Research, 2023)

Thanatology in the northern muriqui (Brachyteles hypoxanthus) - Robério Freire Filho; Igor Inforzato; Fernanda P. Tabacow; Waldney Martins; Carla B. Possamai; Daniel Ferraz; Robson O. E. Hack; Samantha Rocha; Daniel V. Slomp; Marcello S. Nery; Letícia Almeida; Naíla Fernandes; et al. (Primates, 2022)

Rivastigmine Reverses the Decrease in Synapsin and Memory Caused by Homocysteine: Is There Relation to Inflammation? - Osmar Vieira Ramires Junior; Tiago Marcon dos Santos; Josiane Silva Silveira; Raíssa Leite-Aguiar; Robson Coutinho-Silva; Luiz Eduardo Baggio Savio; Angela T. S. Wyse (Molecular Neurobiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Editorial: Plastic Ingestion: Understanding Causes and Impacts - Matthew S. Savoca; Gabriel E. Machovsky-Capuska; Ryan Andrades; Robson G. Santos (Frontiers in Marine Science, 2022)

Folic acid supplementation during pregnancy alters behavior in male rat offspring: nitrative stress and neuroinflammatory implications - Josiane Silva Silveira; Osmar Vieira Ramires Júnior; Felipe Schmitz; Fernanda Silva Ferreira; Fabiana Cristina Rodrigues; Robson Coutinho Silva; Luiz Eduardo Baggio Savio; Angela T. S. Wyse (Molecular Neurobiology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

Recognizing the enemy: do predator cues influence hatching in Neotropical annual killifish? - Robson S. Godoy; Vinicius Weber; Luis Esteban Krause Lanés; Martin Reichard; Tanise Gemelli; Raquel Von Hohendorff; Leonardo Maltchik (Journal of Fish Biology, 2021)
Annual fish species have evolved complex adaptations to survive in temporary wetlands. The main adaptation of these fish is the ability to produce embryos that survive dry periods. Embryo development of this fish can show variation at multiple levels influenced by many environmental factors, such as photoperiod and temperature. Predator cues are another factor that can influence the embryonic stage. One way in which annual fish could adapt to predators is by using risk‐spreading strategies (through bet‐hedging). Nonetheless, this strategy depends on the coevolutionary history between predators and preys and on the degree of environmental unpredictability, resulting in different responses across different species. This study investigated the influence of predator cues on the embryonic development and hatching of two Austrolebias species that inhabit ponds that present differences in hydroperiod and the risk of predator presence. The results confirmed a differentiated response between the two annual fish species tested, corroborating the modulation of hatching against the risk of predation by native predatory fish. The authors further showed that development times varied between the two annual fish species, regardless of the presence of predators. They highlight that the variation in embryonic development is strongly affected by different levels of hydroperiod unpredictability faced by the two species. To unravel finer‐scale local adaptations in the annual fish embryo development, future studies should focus on a region with greater spatial gradient.

Propolis and Lentinula edodes extracts can control the angular leaf spot of strawberry by different mechanisms - Bruna Rodrigues; Danila S. O. Coqueiro; Robson M. Di Piero (Journal of Plant Pathology, 2021)

Historical and future drought impacts in the Pacific islands and atolls - Viliamu Iese; Anthony S. Kiem; Azarel Mariner; Philip Malsale; Tile Tofaeono; Dewi G.C. Kirono; Vanessa Round; Craig Heady; Robson Tigona; Filipe Veisa; Kisolel Posanau; Faapisa Aiono; et al. (Climatic Change, 2021)
Drought is known as a “creeping disaster” because drought impacts are usually noticed months or years after a drought begins. In the Pacific Island Countries and Territories (PICTs), there is almost no ability to tell when a drought will begin or end, especially for droughts other than meteorological droughts. Monitoring, forecasting and managing drought in the PICTs is complex due to the variety of different ways droughts occur, and the diverse direct and indirect causes and consequences of drought, across the PICT region. For example, the impacts of drought across the PICTs vary significantly depending on (i) the type of drought (e.g. meteorological drought or agricultural drought); (ii) the location (e.g. high islands versus atolls); (iii) socioeconomic conditions in the location affected by drought; and (iv) cultural attitudes towards the causes of drought (e.g. a punishment from God versus a natural process that is potentially predictable and something that can be managed). This paper summarises what is known and unknown about drought impacts in the PICTs and provides recommendations to guide future research and investment towards minimising the negative impacts of droughts when they inevitably occur in the PICTs.

Carbapenem-Resistant Pseudomonas aeruginosa in Chronic Lung Infection: Current Resistance Profile and Hypermutability in Patients with Cystic Fibrosis - Mila M. Almeida; Meyvianne T. Freitas; Tania W. Folescu; Monica C. Firmida; Ana Paula D’A. Carvalho-Assef; Elizabeth A. Marques; Robson S. Leão (Current Microbiology, 2021)

Localization of angiotensin-(1-7) and Mas receptor in the rat ovary throughout the estrous cycle - Virginia M. Pereira; Fernando M. Reis; Geovanni D. Cassali; Sergio H. S. Santos; Maira Casalechi; Robson A. S. Santos; Adelina M. Reis (Journal of Molecular Histology, 2020)

Basal resource quality and energy sources in three habitats of a lowland river ecosystem - Paul J. McInerney; Galen Holt; Rebecca E. Lester; Ross M. Thompson; Barbara Robson; Darren S. Ryder; Nick R. Bond; Darren S. Baldwin; Ben Gawne; Rochelle Petrie (Limnology and Oceanography, 2020)
Understanding energy flow through ecosystems and among sub‐habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats—river channels, anabranches and wetlands—of a lowland river floodplain in the Murray River catchment, Australia during a period of disconnected surface flow. We used a combination of stable isotope and fatty acid analyses to determine which basal resources were assimilated by the backswimmer Anisops thienemanni and the Eastern mosquitofish Gambusia holbrooki and assessed food quality across the three habitats. Seston was a primary basal resource for both animals in all three habitats, but was of higher quality within floodplain habitats than in the river channel. Although floodplain seston contained higher concentrations of essential fatty acids, fatty acid profiles of animals from different habitats remained similar. Our research suggests that inundation of floodplains and subsequent reconnection to the river could be valuable to afford riverine animals the opportunity to access high quality resources, but highlights a need to quantitatively assess the transfer of essential fatty acids between trophic levels to determine how much riverine animals are in fact limited by poorer quality food resources. We demonstrate the importance of estimating the quality of organic matter fluxes into food webs, and the potential role of targeted environmental flows to re‐establish high quality energy pathways in riverine ecosystems.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Unexpected but unsurprising lineage diversity within the most widespread Neotropical crocodilian genus Caiman (Crocodylia, Alligatoridae) - Igor J. Roberto; Pedro S. Bittencourt; Fabio L. Muniz; Sandra M. Hernández-Rangel; Yhuri C. Nóbrega; Robson W. Ávila; Bruno C. Souza; Gustavo Alvarez; Guido Miranda-Chumacero; Zilca Campos; Izeni P. Farias; Tomas Hrbek (Systematics and Biodiversity, 2020)

Oxidative stress resistance in a short-lived Neotropical annual killifish - Robson S. Godoy; Luis Esteban K. Lanés; Bruna D. Castro; Vinicius Weber; Natália Wingen; Mateus M. Pires; Guendalina T. Oliveira; Leonardo Maltchik (Biogerontology, 2020)

Comparative larval ontogeny of two fish species (Characiformes and Siluriformes) endemic to the São Francisco River in Brazil - Maíra S. A. Rocha; Robson C. Silva; José C. E. Santos; Marianne Schorer; Maria P. Nascimento; Marcelo M. Pedreira (Journal of Fish Biology, 2020)
The aim of the present study was to perform comparative histological analyses of the ontogenetic development of two fish species endemic to the São Francisco River in Brazil: Prochilodus argenteus and Lophiosilurus alexandri . Histological analyses were performed every 24 h from the moment of hatching until 14 days post‐hatching (dph) for the observation of larval development and until 39 dph for the observation of gonadal development. Whole larvae were fixed in Bouin's solution and the histological slides were stained with haematoxylin–eosin. Lophiosilurus alexandri larvae had a larger body size compared with P. argenteus larvae since hatching. Lophiosilurus alexandri larvae had mouth opening and pigmentation of the eyes upon hatching, whereas these events were observed at 1 dph in P. argenteus larvae. The visualisation and the inflation of the swim bladder occurred at 1 and 3 dph, respectively, in the P. argenteus , whereas these events occurred at 2 and 8 dph, respectively, in L. alexandri . Yolk granules were absorbed at 4 dph in P. argenteus and the 10 dph in L. alexandri . At 7 dph, the digestive tube was more differentiated in L. alexandri than P. argenteus and at 14 dph, the digestive system of both species had features of their eating habits: broad stomach and short intestine in L. alexandri , typical of carnivorous habits; stomach with a mechanical function and long intestine in P. argenteus , typical of detritivorous habits. The epithelial lining tissue, formed by a single layer of cells in the newly hatched larvae (0 dph), differentiated throughout the study, exhibiting scales in P. argenteus and numerous club cells in the middle epithelial region of L. alexandri at 39 dph. Undifferentiated gonads with somatic cells and primordial germ cells were observed at 39 dph, with caudal‐cranial migration since 1 dph in both species. The anatomic changes during the ontogeny of P. argenteus and L. alexandri larvae are directly associated with the evolutionary history of each species, which explains their feeding habits, behaviour and distribution in the environment: Prochilodus argenteus is detritivorous and actively swims in the water column, whereas L. alexandri is carnivorous and inhabits bottom regions. At 39 dph neither species exhibited sexual differentiation.

Age-associated liver alterations in wild populations of Austrolebias minuano, a short-lived Neotropical annual killifish - Robson S. Godoy; Luis Esteban K. Lanés; Vinicius Weber; Cristina Stenert; Héctor G. Nóblega; Guendalina T. Oliveira; Leonardo Maltchik (Biogerontology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

In situ phytoremediation characterization of heavy metals promoted by Hydrocotyle ranunculoides at Santa Bárbara stream, an anthropogenic polluted site in southern of Brazil - Carolina F. Demarco; Thays F. Afonso; Simone Pieniz; Maurízio S. Quadro; Flávio A. O. Camargo; Robson Andreazza (Environmental Science and Pollution Research, 2018)

Intralesional uridine-5′-triphosphate (UTP) treatment induced resistance to Leishmania amazonensis infection by boosting Th1 immune responses and reactive oxygen species production - Camila Marques-da-Silva; Mariana M. Chaves; Maria Luiza Thorstenberg; Vanessa R. Figliuolo; Flávia S. Vieira; Suzana P. Chaves; José Roberto Meyer-Fernandes; Bartira Rossi-Bergmann; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva (Purinergic Signalling, 2018)

Environmental predictors for annual fish assemblages in subtropical grasslands of South America: the role of landscape and habitat characteristics - Luis Esteban Krause Lanés; Martin Reichard; Rafael Gomes de Moura; Robson S. Godoy; Leonardo Maltchik (Environmental Biology of Fishes, 2018)

Treatment with pentylenetetrazole (PTZ) and 4-aminopyridine (4-AP) differently affects survival, locomotor activity, and biochemical markers in Drosophila melanogaster - Deividi C. S. Soares; José L. R. Portela; Daniel H. Roos; Nathane R. Rodrigues; Karen K. Gomes; Giulianna E. Macedo; Thais Posser; Jeferson L. Franco; Waseem Hassan; Robson L. Puntel (Molecular and Cellular Biochemistry, 2018)

Kinin Receptors Sensitize TRPV4 Channel and Induce Mechanical Hyperalgesia: Relevance to Paclitaxel-Induced Peripheral Neuropathy in Mice - Robson Costa; Maíra A. Bicca; Marianne N. Manjavachi; Gabriela C. Segat; Fabiana Chaves Dias; Elizabeth S. Fernandes; João B. Calixto (Molecular Neurobiology, 2018)

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Erratum to: Reptile surveys reveal high species richness in areas recovering from mining activity in the Brazilian Cerrado - Fabrício H. Oda; Robson W. Ávila; Leandro O. de Drummond; Danusy L. Santos; Priscilla G. Gambale; Vinicius Guerra; Raísa Romęnia S. Vieira; Tiago S. Vasconcelos; Rogério P. Bastos; Fausto Nomura (Biologia, 2017)

P2X7 Receptor Signaling Contributes to Sepsis-Associated Brain Dysfunction - Luiz Eduardo Baggio Savio; Mariana G. Juste Andrade; Paola de Andrade Mello; Patrícia Teixeira Santana; Aline Cristina Abreu Moreira-Souza; Janaína Kolling; Aline Longoni; Linda Feldbrügge; Yan Wu; Angela T. S. Wyse; Simon C. Robson; Robson Coutinho-Silva (Molecular Neurobiology, 2017)

Reptile surveys reveal high species richness in areas recovering from mining activity in the Brazilian Cerrado - Fabrício H. Oda; Robson W. Ávila; Leandro de O. Drummond; Danusy L. Santos; Priscilla G. Gambale; Vinicius Guerra; Raísa Romênia S. Vieira; Tiago S. Vasconcelos; Rogério P. Bastos; Fausto Nomura (Biologia, 2017)

Bj-PRO-5a and Bj-PRO 10c Found at C-Type Natriuretic Peptide Precursor of Bothrops jararaca Change Renal Function of Hypertensive Rats - Carlos H. Xavier; José Rodolfo R. Miranda; Juliana Yamaguchi; Kátia D. da Silveira; Mauro M. Teixeira; Deoclécio Alves Chianca-Jr; Ana C. Simões e Silva; Robson A. S. Santos; Antônio C. M. Camargo; Danielle Ianzer (International Journal of Peptide Research and Therapeutics, 2017)

Structural evolution of a normal fault array in the Gambier Embayment, offshore Otway Basin, South Australia: insights from 3D seismic data - A. G. Robson; S. P. Holford; R. C. King (Australian Journal of Earth Sciences, 2017)

Spatialization of Brazilian pig production: relationship between productive, physical, environmental, and socio-economic variables - Isabel C. M. da Silva; Bárbara Bremm; Jennifer L. Teixeira; Nathalia S. Costa; Júlio O.J. Barcellos; José Braccini; Robson J. Cesconeto; Concepta McManus (Tropical Animal Health and Production, 2017)

Recent Progress in Understanding and Predicting Atlantic Decadal Climate Variability - S. G. Yeager; J. I. Robson (Current Climate Change Reports, 2017)

Planning and management for sustainable coastal aquaculture development in Santa Catarina State, south Brazil - Felipe M. Suplicy; Luiz F. de Novaes Vianna; Guilherme S. Rupp; André L. T. Novaes; Luis H. P. Garbossa; Robson V. de Souza; João Guzenski; Sérgio W. da Costa; Fabiano M. Silva; Alex A. dos Santos (Reviews in Aquaculture, 2017)
Marine aquaculture of bivalve molluscs is an important economic activity in Santa Catarina State, Brazil, with more than 5000 persons directly and indirectly involved and an annual revenue of US $ 18 million in 2013. In the first decade of this activity, a lack of proper regulation imposed multiple obstacles to the sustainable management of local shellfish farming. The occupation of marine space occurred in a disorderly manner, and the unplanned development led to unfavourable conditions that threatened the sustainability of the industry. This study describes how better planning and management tools have improved governance of marine aquaculture in Santa Catarina State. The process included development of a legal framework for aquaculture planning, elaboration of local development plans with a participatory and multidisciplinary approach, development of a geographic information system to identify favourable areas and creation of a Web‐based aquaculture management system. The combined application of these actions, along with continuing extension services, is expected to contribute to the regulation of 837 shellfish farming areas, the expansion of farming activity, the mitigation of the environmental and visual impacts caused by coastal aquaculture and an increase in the public health of shellfish consumers. In this manuscript, we report an example of how the application of better planning and management of the aquaculture sector can prepare the industry for a sustainable growing cycle.

Cu(II) adsorption from copper mine water by chitosan films and the matrix effects - Tuanny S. Frantz; Nauro Silveira; Maurízio S. Quadro; Robson Andreazza; Amauri A. Barcelos; Tito R. S. Cadaval; Luiz A. A. Pinto (Environmental Science and Pollution Research, 2017)

Thermotolerant coliform loadings to coastal areas of Santa Catarina (Brazil) evidence the effect of growing urbanisation and insufficient provision of sewerage infrastructure - Luis H. P. Garbossa; Robson V. Souza; Carlos J. A. Campos; Argeu Vanz; Luiz F. N. Vianna; Guilherme S. Rupp (Environmental Monitoring and Assessment, 2017)

Exploring, exploiting and evolving diversity of aquatic ecosystem models: a community perspective - Annette B. G. Janssen; George B. Arhonditsis; Arthur Beusen; Karsten Bolding; Louise Bruce; Jorn Bruggeman; Raoul-Marie Couture; Andrea S. Downing; J. Alex Elliott; Marieke A. Frassl; Gideon Gal; Daan J. Gerla; et al. (Aquatic Ecology, 2015)

Evolutionary transitions of complex labile traits: Silk weaving and arboreal nesting in Polyrhachis ants - Simon K. A. Robson; Rudy J. Kohout; Andrew T. Beckenbach; Corrie S. Moreau (Behavioral Ecology and Sociobiology, 2015)

Removal of Pharmaceuticals and Endocrine Disruptor Compounds from Natural Waters by Clarification Associated with Powdered Activated Carbon - Diego R. S. Lima; Bruno E. L. Baêta; Sérgio F. Aquino; Marcelo Libânio; Robson J. C. F. Afonso (Water, Air, & Soil Pollution, 2014)

Oral administration of angiotensin-(1–7) ameliorates type 2 diabetes in rats - Sérgio H. S. Santos; Jorge F. Giani; Valeria Burghi; Johanna G. Miquet; Fatimunnisa Qadri; Janaina F. Braga; Mihail Todiras; Katarina Kotnik; Natalia Alenina; Fernando P. Dominici; Robson A. S. Santos; Michael Bader (Journal of Molecular Medicine, 2014)

Biodegradation of starch blended polyvinyl chloride films by isolated Phanerochaete chrysosporium PV1 - M. I. Ali; S. Ahmed; I. Javed; N. Ali; N. Atiq; A. Hameed; G. Robson (International Journal of Environmental Science and Technology, 2014)

Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.

Comparative evaluation of different preservation methods for cyanobacterial strains - Alberto A. Esteves-Ferreira; Débora M. Corrêa; Antônio P. S. Carneiro; Rinamara M. Rosa; Robson Loterio; Wagner L. Araújo (Journal of Applied Phycology, 2013)

The value of X-ray approaches in the study of the Messel fruit and seed flora - Margaret E. Collinson; Selena Y. Smith; Steven R. Manchester; Volker Wilde; Lauren E. Howard; Brittany E. Robson; David S. F. Ford; Federica Marone; Julie L. Fife; Marco Stampanoni (Palaeobiodiversity and Palaeoenvironments, 2012)

Tissue specific localization of angiotensin-(1–7) and its receptor Mas in the uterus of ovariectomized rats - João Vaz-Silva; Rubens L. Tavares; Márcia C. Ferreira; Kinulpe Honorato-Sampaio; Ines K. D. Cavallo; Robson A. S. Santos; Adelina M. dos Reis; Fernando M. Reis (Journal of Molecular Histology, 2012)

Overexpression of NTPDase2 in gliomas promotes systemic inflammation and pulmonary injury - Elizandra Braganhol; Rafael F. Zanin; Andressa Bernardi; Leticia S. Bergamin; Angelica R. Cappellari; Luis F. Campesato; Fernanda B. Morrone; Maria M. Campos; João B. Calixto; Maria Isabel A. Edelweiss; Márcia R. Wink; Jean Sévigny; et al. (Purinergic Signalling, 2012)

Scanning Electron Microscopy and Fermentation Studies on Selected Known Maize Starch Mutants Using STARGEN™ Enzyme Blends - Jessica M. M. Adams; Pauline J. M. Teunissen; Geoff Robson; Nigel Dunn-Coleman; Iain S. Donnison (BioEnergy Research, 2012)

Colony genetic structure in the Australian jumper ant Myrmecia pilosula - Z.-Q. Qian; B. C. Schlick-Steiner; F. M. Steiner; S. K. A. Robson; H. Schlüns; E. A. Schlüns; R. H. Crozier (Insectes Sociaux, 2012)

A flexible quantitative methodology for the analysis of gene-flow between conventionally bred maize populations using microsatellite markers - P. R. H. Robson; R. Kelly; E. F. Jensen; G. D. Giddings; M. Leitch; C. Davey; A. P. Gay; G. Jenkins; H. Thomas; I. S. Donnison (Theoretical and Applied Genetics, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Weaver ants Oecophylla smaragdina encounter nasty neighbors rather than dear enemies - Philip S. Newey; Simon K. A. Robson; Ross H. Crozier (Ecology, 2010)
The evolution of territorial behavior requires that the benefits of territoriality outweigh the costs. The costs are primarily those of territorial defense against encroaching neighbors or against floaters seeking to establish their own territory. One way to reduce the cost of defense might be to restrict serious conflict to encounters with those posing the greatest threat. Studies of many animals have found that less aggression is shown toward neighbors than toward strangers, a phenomenon known as the “dear enemy” effect. However, the opposite can also be true, namely, that more aggression is shown toward neighbors than strangers: the “nasty neighbor” effect. This may be particularly true of group‐living species that defend a resource‐based territory. Here we show that (1) colonies of the weaver ant Oecophylla smaragdina were able to recognize a greater proportion of workers from neighboring colonies as non‐colony members; and (2) when recognized as non‐colony members, more aggression was exhibited toward neighbors than non‐neighbors. We present for the first time evidence that differential levels of aggression involve both a perceptual and behavioral component. On the other hand, we found no evidence that weaver ant workers were better able to recognize workers from previously unknown colonies or responded more aggressively to them, even after a 10‐day period of contact. This contrasts with other species in which rapid learning of the identity of new potential enemies has been demonstrated. We suggest that such a response is unnecessary for weaver ants, as encounters with intruders from non‐neighboring colonies are probably rare and of little consequence. This study adds to the growing body of evidence that the nasty neighbor effect may be much more common than the dear enemy effect among group‐living species.

Ants as indicators for vertebrate fauna at a local scale: an assessment of cross-taxa surrogacy in a disturbed matrix - J. M. Bennett; A. S. Kutt; C. N. Johnson; S. K. A. Robson (Biodiversity and Conservation, 2009)

Nest and colony-specific spectra in the weaver ant Oecophylla smaragdina - P. Newey; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2009)

Localization of plasma membrane bound NTPDases in the murine reproductive tract - M. Martín-Satué; É. G. Lavoie; J. Pelletier; M. Fausther; E. Csizmadia; O. Guckelberger; S. C. Robson; Jean Sévigny (Histochemistry and Cell Biology, 2009)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Near-infrared spectroscopy identifies the colony and nest of origin of weaver ants, Oecophylla smaragdina - P. S. Newey; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2008)

Bryophyte dispersal by flying foxes: a novel discovery - J. G. Parsons; A. Cairns; C. N. Johnson; S. K. A. Robson; L. A. Shilton; D. A. Westcott (Oecologia, 2007)

Social and genetic structure of a supercolonial weaver ant, Polyrhachis robsoni, with dimorphic queens - J. S. van Zweden; M. E. Carew; M. T. Henshaw; S. K. A. Robson; R. H. Crozier (Insectes Sociaux, 2007)

The structure of a micro-bat community in relation to gradients of environmental variation in a tropical urban area - C. L. Hourigan; C. Johnson; S. K. A. Robson (Urban Ecosystems, 2006)

Immature Steller sea lion ( Eumetopias jubatus ) dive activity in relation to habitat features of the eastern Aleutian Islands - BRIAN S. FADELY; BRUCE W. ROBSON; JEREMY T. STERLING; ANGIE GREIG; KATHERINE A. CALL (Fisheries Oceanography, 2005)
Current flow and bathymetry in the Aleutian Islands define unique habitats that influence prey distribution and foraging behaviour of top‐level predators. We explored whether oceanographic features and bathymetry influenced the diving activity of 30 immature sea lions (ages 5–21 months) equipped with satellite‐linked depth recorders in the eastern Aleutian Islands (EAI) during 2000–02. Sea surface temperature (SST) and chlorophyll a concentrations were obtained from remote sensing satellite imagery and associated with locations where sea lion diving was recorded. Most locations associated with diving to >4 m were within 10 nautical miles (nm) of shore and associated with onshelf waters a concentrations, but also with sea lion age. Associations with habitat features did not consistently explain variability in dive count, time at depth, dive focus or focal depth. Nearshore diving tended to be influenced by distance from shore or seafloor depth, whereas increased SST coincided with activity of sea lions diving >30 nm offshore. Immature sea lions developing into independent foragers in the relatively shallow pass areas of the EAI do so at a time of rapid changes in oceanography and prey availability.

Comparative hydrolysis of P2 receptor agonists by NTPDases 1, 2, 3 and 8 - F. Kukulski; S. A. Lévesque; É. G. Lavoie; J. Lecka; F. Bigonnesse; A. F. Knowles; S. C. Robson; T. L. Kirley; J. Sévigny (Purinergic Signalling, 2005)

The origin and spread of the HFE-C282Y haemochromatosis mutation - S. Distante; K.J.H. Robson; J. Graham-Campbell; A. Arnaiz-Villena; P. Brissot; Mark Worwood (Human Genetics, 2004)

Modification of senescence in ryegrass transformed with IPT under the control of a monocot senescence-enhanced promoter - Q. Li; P. R. H. Robson; A. J. E. Bettany; I. S. Donnison; H. Thomas; I. M. Scott (Plant Cell Reports, 2004)

Angiotensin-(1–7) stimulates water transport in rat inner medullary collecting duct: evidence for involvement of vasopressin V2 receptors - Antonio J. Magaldi; Katia R. Cesar; Magali de Araújo; Ana C. Simões e Silva; Robson A. S. Santos (Pflügers Archiv - European Journal of Physiology, 2003)

The formation, morphology and anatomy of cluster root of Lupinus albus L. as dependent on soil type and phosphorus supply - C. S. Peek; A. D. Robson; J. Kuo (Plant and Soil, 2003)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Conserved structure and function of the Arabidopsis flowering time gene CONSTANS in Brassica napus - Laurian S. Robert; Frances Robson; Andrew Sharpe; Derek Lydiate; George Coupland (Plant Molecular Biology, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)